A look at the role of the lacemaker woman in the Brazilian fashion history (ModaPalavra e-periódico, 2015)
This article aims to study the role of the lacemaker woman in the Brazilian society, discussing the changes, the gain of knowledge and the reinterpretation of lace made by hand in the twentieth and twenty-first century. For this, it ́s based on the analysis of social and cultural aspects as well as the approach the micro-history life of the elite lady of Rio de Janeiro, lace maker, consumer and collector. Analyzing the two main social settings, the elite and the working class, it was found that lace production relation, in all the centuries studied, have changed due to the current model of women's live.
Keywords: fashion history; lace maker woman; brazilian society